DATING VIOLENCE PREVENTION PROGRAMS IN COLLEGE STUDENTS: A SYSTEMATIC LITERATURE REVIEW - Ningrum, Andini Puspa; Fitri, Susi; Herdi, Herdi (LP2M IAI Al-Khairat Pamekasan, 2025)
This study aims to evaluate the effectiveness of various dating violence prevention programs among college students through a systematic literature review guided by PRISMA. Article searches were conducted using the publish or perish application with three databases, Google Scholar, Scopus, and Semantic Scholar. Seven articles from various databases were qualitatively analyzed to identify intervention approaches, effectiveness, and relevance to higher education settings. Findings indicate that most programs, such as SHARe, DRIVEN, Stepping Up, and SPoRT, adopted a group-based psychoeducational approach that effectively increased awareness, communication skills, and attitudes toward healthy relationships. Media-based interventions such as the STOP Dating Violence Video and visual campaigns such as the Red Flag Campaign also showed positive results in increasing bystander knowledge and efficacy. The SSS program highlighted the importance of social support for survivors. This review recommends the integration of educational, social, and media-based approaches as a comprehensive and contextually relevant prevention strategy for universities in Indonesia.